Floristic composition and green infrastructure designs in the National Park. San Jose, Costa Rica - Acosta-Vargas, Luis Guillermo (2023)
Cities concentered 65% world´s population, causing ecosystem deterioration where they are located and limiting the enjoyment of their diversity and ecosystem services. Given the importance of green spaces within cities, we studied the National Park (NP) floristic composition and its relationship with the immediate context. The PN is part of the Paseo de las Damas complex together with the Morazán and España parks. The NP has a formal design and is circumscribed in a 101 X 200 m rectangle, with a total area of 19,270 m2, and it is delimited by paved streets, while its sidewalks present a better integration with the park. We surveyed the herbs, and for trees, we measured their diameter, total height, crown height, and crown diameter. For infrastructure, we measured and drew the facades’ profiles on the park’s sides. We recorded 131 plant species belonging to 55 botanical families, of which 58% are introduced and the most abundant (59%). Some of the introduced species are Cupressus lusitanica and Casuarina equisetifolia, which are mixed with native species such as Cedrela odorata. Crown occupation reaches 56% of the park´s area and is concentrated in the middle stratum with 53% of the total. Shrub composition is dominated by exotic species such as Duranta erecta, Schefflera arboricola, and Rhododendron sp., often used as hedges accompanying walls and monuments. Comparatively, the NP shares similar features with the España and Morazán parks; however, due to its larger size, it houses greater biodiversity, and the services are increased. The PN constitutes a reservoir of the Central Valley biodiversity, and management will contribute to improving conservation and a more significant and better provision of ecosystem services.